Zeolite Nanoparticles: The Eco-Friendly Solutions for Environmental Contamination - Sisubalan, Natarajan; Sivamaruthi, Bhagavathi Sundaram; Kesika, Periyanaina (Current Nanoscience, 2026)
This review highlighted the innovative utilization of zeolite Nanoparticles (NPs) in various environmental applications, emphasizing their role in transforming waste materials into valuable resources. Zeolite-confined metal NPs, particularly Palladium (Pd), exhibit enhanced catalytic performance in the deep oxidation of light alkanes due to their unique interfaces and protective zeolite structures. Developing electrospun membranes incorporating cellulose acetate and nano-zeolites demonstrates promising potential for effective oil removal from wastewater, achieving up to 97% separation efficiency. The synthesis of silver NPs from Tilapia fish waste and their valorization within natural zeolites showcases an eco-friendly approach for ammonia removal and antimicrobial applications. Integrating nano-silicon and nano-zeolite treatments in combating salinity stress in medicinal plants highlights sustainable agricultural practices. This review emphasizes the multifaceted benefits of zeolite NPs in addressing urgent environmental challenges and promotes future research directions to optimize their applications in pollution control and resource recovery. Prospects include scaling up production methods, exploring novel composite materials, and investigating the long-term environmental impacts of these nanomaterials to enhance their practical applicability in diverse settings.
Keywords: Water treatment